Klassische Moderne / Sammlung Berg im Karl Ernst Osthaus-Museum. (Hagen : Karl Ernst Osthaus-Museum, 1988)
Corinth, Lovis ; Feininger, Lyonel ; Guillaumin, Armand ; Heckel, Erich ; Jawlensky, Alexej ; Kirchner, Ernst Ludwig ; Liebermann, Max ; Lace, Maximilien ; Müller, Otto ; Nolde, Emil ; Pechstein, Max ; Renoir, Pierre-Auguste ; Rohlfs, Christian ; Rottluff, Karl Schmidt ; Beckmann, Max ; Dix, Otto ; Macke, August ; Marc, Franz ; Schlemmer, Oskar ; van de Velde, Henry
Klassische Moderne / Sammlung Berg im Karl Ernst Osthaus-Museum, Karl Ernst Osthaus-Museum, Hagen, 1989
boek